Identification Of Rhodamine-B And Characteristics Of Bulk Strawberry Jam In Yogyakarta City Market - Nanda Novie Anggraini; Diah Puspitasari; Kurnia Mar’atus Solichah (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2026)
Food safety is a crucial aspect in ensuring health, especially by ensuring that food products are free from hazardous substances. Rhodamine-b is a hazardous synthetic dye used in non-food industries such as paper, ink, and textiles, but its use in food products is prohibited because it is toxic and potentially triggers health issues. Nevertheless, its use is still often found in food as a red dye, including bulk jams sold without trademarks or BPOM distribution permits. Bulk jam, especially strawberry jam, is often given additional coloring to enhance its visual appeal. Thus, this study aims to detect the presence of Rhodamine-b qualitatively and quantitatively, as well as to determine the characteristics of bulk strawberry jam circulating in the Yogyakarta City Market. The research was conducted using both qualitative and quantitative approaches. Qualitative tests were conducted using a Rhodamine-b test kit, while quantitative tests were performed using UV-Vis Spectrophotometry. Market sample collection was carried out using random sampling techniques at 12 markets. Sample collection was done directly at the designated markets. The research results show that no Rhodamine-b content was found in all samples of bulk strawberry jam in Yogyakarta City, both qualitatively and quantitatively, and this is further supported by color testing which did not show any color indicating the presence of Rhodamine-b. The pH testing results indicated that all samples had an appropriate pH. However, 9 out of 12 samples had an appropriate sugar content. This research is expected to contribute to supporting stricter food safety monitoring and raising consumer awareness of the dangers of illegal synthetic dyes in food products. Keyword: Jam; Rhodamine-b; test kit; UV-Vis spectrophotometry